Contraceptive and Infertility Target DataBase: a contraceptive drug development tool for targeting and analysis of human reproductive specific tissues†. Issue 6 (11th September 2021) - Sinha, Subarna; Knapp, Merrill; Pywtorak, John; McCain, Greg; Wingerden, Kenneth; VanDervoort, Colin; Gondek, J Mark; Madrid, Peter; Parman, Toufan; Gerrard, Stephen; Long, Jill E; Blithe, Diana L; et al.
Abstract: The long and challenging drug development process begins with discovery biology for the selection of an appropriate target for a specific indication. Target is a broad term that can be applied to a range of biological entities such as proteins, genes, and ribonucleic acids (RNAs). Although there are numerous databases available for mining biological entities, publicly available searchable, downloadable databases to aid in target selection for a specific disease or indication (e.g., developing contraceptives and infertility treatments) are limited. We report the development of the Contraceptive and Infertility Target DataBase (https://www.citdbase.org ), which provides investigators an interface to mine existing transcriptomic and proteomic resources to identify high-quality contraceptive/infertility targets. The development of similar databases is applicable to the identification of targets for other diseases and conditions. Abstract : Contraceptive and Infertility Target DataBase is a searchable and downloadable database open to the public for the identification of contraceptive/infertility transcriptomic and proteomic targets. Graphical abstract: